Current Approaches to PANS/PANDAS Diagnostics and Management - Inna A. Kostik; Mikhail M. Kostik ("Paediatrician" Publishers LLC, 2020)
PANS, or Pediatric Acute-onset Neuropsychiatric Syndrome, is characterized by the sudden onset of obsessive-compulsive syndrome and accompanied by anxiety, emotional lability and other symptoms. PANDAS, or Pediatric Autoimmune Neuropsychiatric Disorder Associated with Streptococcal Infections, is a subtype of PANS. Modern data on PANS/PANDAS etiology, pathogenesis, diagnostics and management is presented in this article. Therapeutic decisions on using anti-inflammatory and immunotropic therapy including non-steroidal anti-inflammatory drugs, glucocorticoids, intravenous immunoglobulin, plasmapheresis, rituximab and mycophenolate mofetil are analysed.